Anxiety and facial self-contacts: possible impact on COVID-19 transmission in dental practice - María Carrillo-Diaz; Laura Lacomba-Trejo; Antonio del Valle-González; Martín Romero-Maroto; María José González-Olmo (BMC, 2021)
Abstract Background The purpose was to analyse the associations between dental and trait anxiety, fear of COVID-19 and the duration and frequency of spontaneous hand-to-face contact (self-contact). Methods A cross-sectional design was carried out with 128 adult patients from four dental clinics in Madrid, during the confinement, from March 15 to May 15. The patients' movements in the waiting room were monitored with Microsoft Kinect Software, also completed the Trait anxiety subscale of the STAI, the COVID-19 Fear and the S-DAI questionnaire. Results Associations were observed between the duration and frequency of facial, mask and eye contact with trait anxiety and dental fear was determined only by the frequency of this self-contact. Trait anxiety is associated with dental anxiety and with fear of COVID-19. Although facial self-contact is higher in women, it also rises in men as dental fear increases. Moreover, dental anxiety is a good predictor of trait anxiety and the incidence of facial self-contact. Conclusions Understanding the possible associations between biopsychosocial factors, such as trait anxiety, dental anxiety and self-contact is important. It may help to prevent the spread of COVID-19 in the population as well as enabling the formulation of effective interventions to improve oral health care through the implementation of dental care programmes.